Head and neck ultrasonography : essential and extended applications - Orloff, Lisa A. (Plural Publishing, Inc., 2017)
This is a comprehensive text of point-of-care ultrasonography for clinicians who manage patients with head and neck disorders. The Second Edition has been revised to bring the reader up to date in expanded applications of real-time ultrasonography for the spectrum of conditions that affect the head and neck region in adults and children alike. It provides new insights, pearls, and practical lessons in ultrasonography for the student of head and neck anatomy, the novice ultrasonographer, and the experienced surgeon or specialist.